(untitled) (Altre Modernità, 2017)
Unlike the hard sciences, historiography lacks a specific nomenclature. The lexicon employed by historians is drawn from the plain language of everyday life. Therefore, the words of history are to be defined within the spatio-temporal framework, and to be construed through processes of contextualization and comparison. My work here stems from these considerations, and attempts to chart the occurrence of errors in historiography. In particular, I take into account the way in which historiographic mistakes arise from the intermingling of words, space, and historical time. Another significant aspect concerns the relationship between history, fiction, and arbitrariness. The latter concept is linked to historical interpretation, which constitutes the last stage of historiographical work, after the analysis and the reconstruction of events. The last part of this paper offers a typology of frequent errors in historiography.